Sustainability assessment of the whole biomass-to-energy chain of a combined heat and power plant based on biomass gasification: biomass supply chain management and life cycle assessment. (1st September 2022) - Costa, Michela; Piazzullo, Daniele; Di Battista, Davide; De Vita, Angelo
Abstract: Energy generation from waste renewable sources represent an efficient way to provide green power with the highest environmental benefits, tackling problems related to the high costs for their disposal through the conversion of these wastes in biofuels. However, several challenges hinder their intensified use, as the huge variability in the amount and composition of these sources forces authors to enlarge their studies on the entire biomass-to-energy chain sustainability where the power technology can be installed with the highest profits. In present work, the technical, environmental and economic impact of the entire biomass-to-energy supply chain is assessed with reference to a real commercially available Combined Heat and Power (CHP) system, the CMD ECO20X based on biomass gasification, installed as operational demonstration in the Municipality of Laurino in the National Park of Cilento, Vallo di Diano, and Alburni (PNCVD) in Southern part of Italy. Several calculation tools previously developed by authors for the analysis of the performance of the various components of the ECO20X system are here employed to define the mass and energy fluxes that characterize its operations in a local supply chain where forest management residues (oak and beech trees) and olive pomace from oil mills in the area are exploited. The analysis aims to quantify the energy absorption necessary for the pretreatment operations of the organic residue (shredding, briquetting, drying) which are essential for gasification, and how much they affect the production deriving from the biomass cogeneration process itself. Then, measurements in terms of pollutants related to the energy production at the municipality and of the air quality in the area, help in the evaluation of the plant environmental impact from a global perspective, by virtue of data obtained from an LCA analysis conducted considering one year functioning of the CHP plant. Highlights: Innovative forest management implemented in a National Park in Southern Italy. Operational demonstration of a real CHP system in the Park. Electrical and thermal demands of pre-treatments processes are covered by ICE production. Technical, environmental, economic impact of the entire biomass-to-energy supply chain. Gasification and combustion phases cover more than 50% of the total LCA impact.